2020
DOI: 10.3390/jcm9030773
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid is Associated with Renal Prognosis of Lupus Nephritis in Women but not in Men

Abstract: Lupus nephritis (LN) is a major complication of systemic lupus erythematosus. Early intervention in lupus nephritis improves prognosis. There is an association between hyperuricemia and lupus nephritis; nevertheless, the sex-specific role of uric acid in lupus nephritis remains unclear. We retrospectively analyzed 578 patients diagnosed with LN by renal biopsy. We determine the relationship of serum uric acid to progression of LN using Kaplan–Meier survival analyses and Cox proportional hazards models. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 42 publications
1
19
1
Order By: Relevance
“…Among the 1297 patients with LN, approximately half of the patients had HUA. In comparison, the prevalence of HUA was 40.11% in a study by Liu et al [ 13 ], and 37.3% in a study by Oh et al [ 14 ]; these rates were lower than that in our study. As already known, UA is excreted predominantly by the kidneys, and its level increases gradually with a decrease in renal function.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Among the 1297 patients with LN, approximately half of the patients had HUA. In comparison, the prevalence of HUA was 40.11% in a study by Liu et al [ 13 ], and 37.3% in a study by Oh et al [ 14 ]; these rates were lower than that in our study. As already known, UA is excreted predominantly by the kidneys, and its level increases gradually with a decrease in renal function.…”
Section: Discussioncontrasting
confidence: 91%
“…Compared to LN patients without HUA, we found that LN patients with HUA presented with higher BP and triglyceride levels; lower hemoglobin and serum albumin levels; worse renal function, hematuria, and proteinuria; higher activity of lupus; and more positive antiphospholipid antibody. A study from Korea showed similar results; their HUA group showed higher creatinine level and blood pressure, lower hemoglobin and serum albumin levels, a lower C3 level, higher anti-dsDNA antibody, lower eGFR, higher total cholesterol, and higher urine protein to creatinine ratio [ 14 ]. Liu et al also reported more hypertension with increases in urine sediment, triglycerides, blood glucose, BUN, serum creatinine, phosphorus, parathyroid hormone, 24-h urinary albumin, 24-h urinary α1-microglobulin, and activity of urine N -acetyl-β D -glucosaminidase (NAG), along with lower eGFR, serum albumin, complement 3, 24-h urinary calcium, urinary volume, and urinary pH in patients with LN and HUA compared to those without HUA [ 13 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hyperuricemia has been associated with AKI, CKD, hypertension, dyslipidemia, diabetes mellitus (DM), stroke, cardiovascular events, and hepatitis B virus-associated glomerulonephritis [10][11][12][13][14][15]. We recently reported that hyperuricemia was also a risk factor for progression of immunoglobulin A nephropathy and lupus nephritis in women [16,17]. However, little is known about the effect of uric acid on progression to ESRD in patients with MCD.…”
Section: Introductionmentioning
confidence: 99%
“…102,103 In one study, every 1 mg/dl increase in baseline uric acid level increased the risk of lupus nephritis (LN) progression by 15.1% in women. 104 An independent association between serum urate levels and renal allograft outcome has also been reported. [105][106][107] A retrospective analysis of 2993 kidney transplant recipients showed that low and normal serum urate levels within the first year were an independent predictor of better renal allograft outcomes in the long-term follow-up period compared with high serum urate values.…”
Section: Hyperuricemia and Chronic Kidney Diseasementioning
confidence: 92%